Dietary Lasia spinosa Thw. Improves Growth Performance in Broilers - Zhang, Lang; Hong, Yongxing; Liao, Yuying; Tian, Kui; Sun, Haodong; Liu, Xingting; Tang, Yanfei; Hassanin, Abdallah A.; Abdelnour, Sameh A.; Suthikrai, Wanwipa; Srisakwattana, Kittiya; Tharasanit, Theerawat; et al. (Frontiers in Nutrition, 2022)
This study aimed to evaluate the effects of dietary Lasia spinosa Thw. (LST) powder supplementation on growth performance, blood metabolites, antioxidant status, intestinal morphology, and cecal microbiome in broiler chickens. A total of 400 1-day-old male Guangxi partridge broilers (initial body weight: 42.52 ± 0.06 g) were randomly allotted to 4 dietary treatments: LST0 group (a basal diet), LST1 group (a basal diet with 1% LST powder), LST2 group (a basal diet with 2% LST powder), LST4 group (a basal diet with 4% LST powder), 10 replicates for each treatment, and 10 broilers in each treatment group. Results indicated that the average daily feed intake of broilers during 22–42 days and the average daily gain of chickens during 1–42 days significantly increased by dietary supplementation of LST powder (p < 0.01), while the feed conversion ratio during the overall periods was decreased by dietary supplementation of LST powder (p < 0.01). Except for the levels of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in liver (p > 0.05), the levels of SOD, catalase (CAT) and GSH-Px in serum, liver, and breast muscle were significantly increased in the LST supplemented groups (p < 0.05), while the levels of reactive oxygen species (ROS) and malondialdehyde (MDA) in serum, liver, and breast muscle were significantly decreased in the LST supplemented groups (p < 0.05). Furthermore, the levels of triglyceride (TG) and low-density lipoprotein cholesterol (LDL-C) were significantly decreased by the addition of dietary LST powder (p < 0.01), while the levels of HDL-C, Ca, Fe, Mg, and P were linearly increased by the addition of dietary LST powder (p < 0.01). With respect to the gut morphometric, crypt depth was significantly decreased by LST supplementation (p < 0.05), while villus height and the ratio of villus height to crypt depth were notably increased by LST supplementation (p < 0.05). Sequencing of 16S ribosomal RNA (16S rRNA) from the cecal contents of broilers revealed that the composition of the chicken gut microbiota was altered by LST supplementation. The α-diversity of microbiota in broilers was increased (p < 0.05) in the LST1 group, but was decreased (p < 0.05) in the LST2 and LST4 groups compared with the LST0 group. The differential genera enriched in the LST1 group, such as Bacillus, Odoribacter, Sutterella, Anaerofilum, Peptococcus, were closely related to the increased growth performance, antioxidant status, intestinal morphology, Ca, Mg, and reduced blood lipid in the treated broilers.